2006
DOI: 10.1136/thx.2005.054643
|View full text |Cite
|
Sign up to set email alerts
|

Inducible NO synthase expression is low in airway epithelium from young children with cystic fibrosis

Abstract: Background: This is the first study to measure inducible nitric oxide synthase (iNOS) gene and protein expression quantitatively in primary epithelial cells from very young children with cystic fibrosis (CF). Low levels of exhaled nitric oxide (NO) in CF suggest dysregulation of NO production in the airway. Due to the importance of NO in cell homeostasis and innate immunity, any defect in the pathway associated with CF would be a potential target for treatment. Methods: Cells were obtained by tracheobronchial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…This humming peak is absent in patients with chronic sinusitis and those with cystic fibrosis [91,95]. There is evidence, in both these conditions, to suggest this is secondary to decreased expression of iNOS, leading to decreased nitric oxide biosynthesis [79,84,85,96].…”
Section: Hypothesis 3: Nitric Oxide Is Trapped In the Obstructed Paramentioning
confidence: 90%
See 1 more Smart Citation
“…This humming peak is absent in patients with chronic sinusitis and those with cystic fibrosis [91,95]. There is evidence, in both these conditions, to suggest this is secondary to decreased expression of iNOS, leading to decreased nitric oxide biosynthesis [79,84,85,96].…”
Section: Hypothesis 3: Nitric Oxide Is Trapped In the Obstructed Paramentioning
confidence: 90%
“…It has also been reported that patients with cystic fibrosis have reduced or absent iNOS expression in the airway epithelia [79,84,85]. A recent study comparing NOS2 and NOS3 mRNA expression (the genes for iNOS and eNOS, respectively) in the nasal mucosa of patients with PCD and secondary ciliary dyskinesia (SCD) found that there was no difference in NOS3 expression but lower levels of NOS2 expression in the PCD group.…”
Section: Decreased Expression Of Nos Isoenzymesmentioning
confidence: 99%
“…The present authors have successfully used this technique to examine biochemical and functional differences in AECs from children with and without asthma [9,10], and inducible nitric oxide responses in young children and infants with CF [11]. However, the increased use of laryngeal mask airways (LMA) in paediatric anaesthesia has significantly decreased the number of children in which this technique is now applicable.…”
mentioning
confidence: 99%
“…In the lungs of patients suffering from CF, epithelial cells fail to produce NO in response to pathogen invasion and bacterial LPS sensing [80,81]. Impaired NO production may be due to reduced NOS expression, including both iNOS [80,82,83] and possibly cNOS [84], as well as reduced availability of the NOS substrate L-arginine, possibly due to increased arginase activity in CF airways [85]. …”
mentioning
confidence: 99%